6(w-1)-3(2+w)=9

Simple and best practice solution for 6(w-1)-3(2+w)=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(w-1)-3(2+w)=9 equation:


Simplifying
6(w + -1) + -3(2 + w) = 9

Reorder the terms:
6(-1 + w) + -3(2 + w) = 9
(-1 * 6 + w * 6) + -3(2 + w) = 9
(-6 + 6w) + -3(2 + w) = 9
-6 + 6w + (2 * -3 + w * -3) = 9
-6 + 6w + (-6 + -3w) = 9

Reorder the terms:
-6 + -6 + 6w + -3w = 9

Combine like terms: -6 + -6 = -12
-12 + 6w + -3w = 9

Combine like terms: 6w + -3w = 3w
-12 + 3w = 9

Solving
-12 + 3w = 9

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 3w = 9 + 12

Combine like terms: -12 + 12 = 0
0 + 3w = 9 + 12
3w = 9 + 12

Combine like terms: 9 + 12 = 21
3w = 21

Divide each side by '3'.
w = 7

Simplifying
w = 7

See similar equations:

| 2x(x+25-10)-2=y | | 3c+6d=18 | | -1(1+7a)-6(7-a)=36 | | 35=5y-55 | | 2(9)+18=36-36 | | 1/4×n=40 | | f(x)=-(-x^3) | | 13=4(-7r-5)-2r | | 5(w+1)=5w-4 | | 15x+12y-36=0 | | y=5y-55 | | a=86/57.98 | | -x^2+5x+7=3 | | x/a=axb | | 3.3x-8.23=8.6 | | 5y-55=5x-30 | | x^2+5x+7=3 | | x+x+-20=26 | | 9h-4-2h=-17 | | x+x+20=26 | | 10(y-3)-10=1 | | ax/a=ab | | -31-9v=-7(6v+8) | | (X+6)(4x+8)+x(x+8)=1 | | 3/5x-3(x-1)=9 | | h^11/h | | 1/7=8/? | | x+x+18=26 | | (X+6)(4x+8)+x(x+8)-1=0 | | 2x-2/3=8 | | 6x-8y-9x+6y=0 | | 7m=796 |

Equations solver categories